2021
DOI: 10.1007/s11307-021-01584-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Initial Characterization of a Reversible, Selective 18F-Labeled Radiotracer for Human Butyrylcholinesterase

Abstract: Purpose A neuropathological hallmark of Alzheimer’s disease (AD) is the presence of amyloid-β (Aβ) plaques in the brain, which are observed in a significant number of cognitively normal, older adults as well. In AD, butyrylcholinesterase (BChE) becomes associated with Aβ aggregates, making it a promising target for imaging probes to support diagnosis of AD. In this study, we present the synthesis, radiochemistry, in vitro and preliminary ex and in vivo investigations of a selective, reversible BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…All procedures used to determine the binding properties of the inhibitors on ChEs have been established before. ,,,,,, …”
Section: Methodsmentioning
confidence: 99%
“…All procedures used to determine the binding properties of the inhibitors on ChEs have been established before. ,,,,,, …”
Section: Methodsmentioning
confidence: 99%
“…Whole physicochemical and neurochemical data, as well as the recent interest devoted to identification of PET tracers based on competitive inhibitors to study the BChE role in AD progression, [ 32,33 ] prompted us to investigate the in vivo ability of 2a to cross BBB and penetrate CNS, and its whole‐body distribution. To do this, we undertook the radiosynthesis of [ 18 F] 2a to study the distribution into the brain and the peripheral organs in mice.…”
Section: Resultsmentioning
confidence: 99%
“…[30] It has been reported that the BChE distribution is involved in the coregulation of cholinergic and noncholinergic neurotransmission at the hippocampal level in humans; therefore, the area-specific effect retrieved might overlap BChE distribution and specific function in that area. [31] Whole physicochemical and neurochemical data, as well as the recent interest devoted to identification of PET tracers based on competitive inhibitors to study the BChE role in AD progression, [32,33] prompted us to investigate the in vivo ability of 2a to cross BBB and penetrate CNS, and its whole-body distribution. To do this, we undertook the radiosynthesis of [ 18 F]2a to study the distribution into the brain and the peripheral organs in mice.…”
Section: Ex Vivo Neurochemical Assaysmentioning
confidence: 99%
“…All procedures used to determine the binding properties of the inhibitors on ChEs have been established before. 19,20,24,26,27,37,[43][44][45][46][47][48]…”
Section: Cholinesterase Inhibitionmentioning
confidence: 99%
“…52 The maximum and minimum number of operations were set to 10 6 and 10 5 with an autoscale factor of 5. As the demethylated carbamate function is supposed to be transferred to the catalytic Ser198 as seen and suggested by several studies, 23,46,53 a constraint was set for the distance between the carbonyl-carbon of the carbamate function and the sidechain oxygen of Ser198 of 2.5-4.0 Å (spring constant = 5.0). The binding site was defined by a radius of 20 Å around the γ-oxygen of Ser198.…”
Section: In Vivo Studiesmentioning
confidence: 99%